MADU MANUKA SEBAGAI TERAPI PENYEMBUHAN LUKA PADA PASIEN ULKUS DIABETIK : LITERATURE REVIEW - Wahyuningtyas, Eka Sakti; Rizkiyani, Anggun Dwi; Handayani, Estrin (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Introduction: Diabetic ulcers are chronic wounds that are difficult to heal due to neurological disorders (neuropathy) and vascular disorders in the legs, causing tissue damage. One way to treat Diabetic Ulcers is by treating wounds using manuka honey. This study aims to determine the effectiveness of giving manuka honey to Diabetic Ulcer patients by literature review. Method: This research is a literature search study using the electronic databases Google Scholar, PubMed, and ScienceDirect. The keywords used in the search were Manuka Honey AND Wound Healing AND Diabetic Ulcers. The inclusion criteria used in the article are accessible, full-text manuscript, in English, free, and journal year used is limited to the last 10 years. Results: The results of the literature study found 6 articles that met the inclusion and exclusion criteria which discussed the use of manuka honey for wound healing in Diabetic Ulcer patients. 6 articles reported that honey shortened the length of wound healing time, increased the rate of bacterial clearance, eradicated infection, accelerated granulation growth, reduced hospitalization time, facilitated debridement, accelerated epithelialization growth and maintained moisture in the wound. Conclusion: 6 articles stated that giving manuka honey was effective in healing wounds in Diabetic Ulcer patients.